Function Identification of Bovine ACSF3 Gene and Its Association With Lipid Metabolism Traits in Beef Cattle - He, Wei; Fang, Xibi; Lu, Xin; Liu, Yue; Li, Guanghui; Zhao, Zhihui; Li, Junya; Yang, Runjun (Frontiers in Veterinary Science, 2022)
Acyl-CoA synthetase family member 3 (ACSF3) carries out the first step of mitochondrial fatty acid synthesis II, which is the linkage of malonate and, to a lesser extent, methylmalonate onto CoA. Malonyl-coenzyme A (malonyl-CoA) is a central metabolite in mammalian fatty acid biochemistry that is generated and utilized in the cytoplasm. In this research, we verified the relationship between expression of the ACSF3 and the production of triglycerides (TGs) at the cellular level by silencing and over-expressing ACSF3. Subsequently, through Sanger sequencing, five polymorphisms were found in the functional domain of the bovine ACSF3, and the relationship between ACSF3 polymorphism and the economic traits and fatty acid composition of Chinese Simmental cattle was analyzed by a means of variance analysis and multiple comparison. The results illustrated that the expression of ACSF3 promoted triglyceride synthesis in bovine mammary epithelial cells and bovine fetal fibroblast cells. Further association analysis also indicated that individuals with the AG genotype (g.14211090 G > A) of ACSF3 were significantly associated with the fatty acid composition of intramuscular fat (higher content of linoleic acid, α-linolenic acid, and arachidonic acid), and that CTCAG haplotype individuals were significantly related to the fatty acid composition of intramuscular fat (higher linoleic acid content). Individuals with the AA genotypes of g.14211055 A > G and g.14211090 G > A were substantially associated with a larger eye muscle area in the Chinese Simmental cattle population. ACSF3 played a pivotal role in the regulation of cellular triacylglycerol and long-chain polyunsaturated fatty acid levels, and polymorphism could serve as a useful molecular marker for future marker-assisted selection in the breeding of intramuscular fat deposition traits in beef cattle.